INTERCURRENCES IN THE NURSING TEAM WORK IN A MEDICAL CLINIC UNIT - Kelly Cristine Alves Pavanati; Alacoque Lorenzini Erdmann (Universidade Federal do Paraná, 2006)
This work is a descriptive study based on a qualitative and quantitative approach, objectifying to analyze the intercurrences in the task routines and in the satisfaction level of the nursing team caused by a temporary absence of a medium-level nursing agent to follow patients for supplementary exams. The data had been obtained from observation of tasks carried out by practitioners and auxiliaries in the morning and afternoon shifts for 3 consecutive days, confronting the data found in the observation with the ones in the institutional routine and standard guide as well as the application of a questionnaire using the interview technique. Thus, it can be noticed that the team is frequently subjected to intercurrences in their work process, however the absence of a team member is the most important factor of anxiety. It is pointed out the importance of reviewing the nursing work organization, inquiring the presence of these problems at an age of complex adaptive systems.